The Potential Correlation Between Nature Engagement in Middle Childhood Years and College Undergraduates’ Nature Engagement, Proenvironmental Attitudes, and Stress - Sachs, Naomi A.; Rakow, Donald A.; Shepley, Mardelle McCuskey; Peditto, Kati (Frontiers in Psychology, 2020)
Introduction: Nature engagement (NE) provides myriad psychological and physiological benefits, many of which begin in childhood and continue into adulthood. Research suggests children who have positive experiences with nature are more likely to continue engaging with nature and have more pro-environmental attitudes (PEA) as adults. Among the benefits of NE are reduced stress, improved sleep and improved cognitive performance, all essential criteria for healthy undergraduate life. College students in particular, due to high levels of stress, may benefit from NE, and the frequency and type of their engagement may be impacted by childhood experience. Objective: This study aimed to better understand the potential correlation between university undergraduates’ past NE in their middle childhood years (MCY) and current NE; past NE and undergraduate PEA; and undergraduate NE and stress levels. We chose to examine the middle childhood and undergraduate years because little research has been conducted on the relationship of NE between these two age groups. Methods: We used a survey of undergraduate students (n = 309) enrolled at a U.S. university to explore the frequency and types of NE during MCY, their family and neighborhood demographics, and current levels of NE, PEA and stress in their undergraduate lives. Results: Although results indicated a large decrease in NE from middle childhood to undergraduate years for most participants, we found a significant positive correlation between NE during MCY and undergraduate NE. We found a positive correlation between MCY NE and undergraduate PEA as well as undergraduate NE and undergraduate PEA. Contrary to other studies and to our hypothesis, we did not find a correlation between undergraduate NE and reduced stress levels. Conclusion: This study looked specifically at U.S. undergraduate students to compare their current engagement with and attitudes toward nature and the environment with their nature experiences during their formative middle childhood years. Our results suggest that it is important for people to have positive experiences with nature in childhood, both for continued NE and to inculcate pro-environmental attitudes in adulthood. These results can help in formulating approaches to improving student well-being at institutions of higher learning.